Impact of indigenous Saccharomyces cerevisiae strains on chemical and sensory profiles of Xinjiang and Ningxia Sauvignon Blanc wines - Xingmeng Lei; Yu Chen; BingHong Gao; Xiaotong Lyu; Haibin Mu; Dongshu Hao; Yi Qin; Yuyang Song; Jiao Jiang; Yanlin Liu (Food Chemistry: X)
This study compared the performance of eight indigenous Saccharomyces cerevisiae strains in fermenting Sauvignon Blanc juice from Ningxia and Xinjiang. While fermentation durations were similar, the strains produced wines with distinct chemical and sensory profiles. Wines fermented with LFN524 and 41y5 had the highest malic acid levels. Volatile analysis revealed differences in terpenes, esters, and higher alcohols, with strains NX16, NX23, and LFN524 showing higher phenylethyl alcohol levels. Strains Wa-318, 182y2, and NX23 produced wines with richer linalool, enhancing floral notes. While aroma profiles of green fruits, citrus, and tropical fruits were similar across Xinjiang wines, Ningxia wines fermented with 41y5 stood out for tropical fruits, red fruits, and blossoms. These findings highlight the potential of indigenous strains to produce fresher Sauvignon Blanc wines with enhanced floral and fruity aromas.